Exploring seebeck-coefficient fluctuations in endohedral-fullerene, single-molecule junctions. Issue 6 (19th April 2022) - Ismael, Ali K.; Rincón-García, Laura; Evangeli, Charalambos; Dallas, Panagiotis; Alotaibi, Turki; Al-Jobory, Alaa A.; Rubio-Bollinger, Gabino; Porfyrakis, Kyriakos; Agraït, Nicolás; Lambert, Colin J.
Abstract : STM measurements and DFT calculations to study 3 bi-thermoelectric endohedral metallofullerenes, benchmarked against C60, show that the fluctuations in S are correlated with the charge inhomogeneity and the geometrical disorder within the junction. Abstract : For the purpose of creating single-molecule junctions, which can convert a temperature difference Δ T into a voltage Δ V via the Seebeck effect, it is of interest to screen molecules for their potential to deliver high values of the Seebeck coefficient S = −Δ V /Δ T . Here we demonstrate that insight into molecular-scale thermoelectricity can be obtained by examining the widths and extreme values of Seebeck histograms. Using a combination of experimental scanning-tunnelling-microscopy-based transport measurements and density-functional-theory-based transport calculations, we study the electrical conductance and Seebeck coefficient of three endohedral metallofullerenes (EMFs) Sc3 N@C80, Sc3 C2 @C80, and Er3 N@C80, which based on their structures, are selected to exhibit different degrees of charge inhomogeneity and geometrical disorder within a junction. We demonstrate that standard deviations in the Seebeck coefficient σ S of EMF-based junctions are correlated with the geometric standard deviation σ and the charge inhomogeneity σ q . We benchmark these molecules against C60 and demonstrate that both σ q, σ S are the largest for Sc3 C2 @C80, both are the smallest for C60 and for the other EMFs, they follow the order Sc3 C2 @C80 > Sc3 N@C80 > Er3 N@C80 > C60 . A large value of σ S is a sign that a molecule can exhibit a wide range of Seebeck coefficients, which means that if orientations corresponding to high values can be selected and controlled, then the molecule has the potential to exhibit high-performance thermoelectricity. For the EMFs studied here, large values of σ S are associated with distributions of Seebeck coefficients containing both positive and negative signs, which reveals that all these EMFs are bi-thermoelectric materials.